Keamanan informasi dalam konteks teknologi komunikasi modern - Habibah, Alifiyah Nur (Maliki Interdisciplinary Journal, 2024)
The rapid development of modern communication technology has changed the way we interact, work, and share information. This article deals with various aspects of information security in the context of modern communication technology, including threats faced, forms of security threats, methods of protection, and best practices. The research issue focuses on the increasing importance of information security in the era of digital transformation and the need for individuals, groups, and governments to implement effective security measures to protect personal information. The methodology used involves reviewing literature to understand the current landscape from information security threats, vulnerabilities, and best practices. Participants include individuals, organizations, and governmental entities involved in information security practices.